THE ROOT OF UNION WITH CHRIST: COMPARISON OF ELECTION IN JOHN CALVIN AND KARL BARTH - Jason Zhao (VERBUM CHRISTI JURNAL TEOLOGI REFORMED INJILI, 2017)
As two of the arguably greatest theologians in church history, both John Calvin and Karl Barth have recognized the significant role of union with Christ and presented it in their works respectively. However, there is no study devoted specifically on the comparison of the two theologians' thoughts regarding this critical theme. This article will start from exploring Calvin and Barth's doctrine of election, the root of their theology of union with Christ. Karl Barth frankly admits that he has departed from Calvin radically on the doctrine of election. While vindicating Barth's assertion, this article further argues that Calvin and Barth's divergent understandings on the root of union with Christ are driven by their contrasting ontological presuppositions. The clarification of that rooted difference will pave the way for our future study of Calvin and Barth's distinctive characterizing of union with Christ.